2018
DOI: 10.1080/15459624.2018.1445260
|View full text |Cite
|
Sign up to set email alerts
|

Airborne contaminants during controlled residential fires

Abstract: In this study, we characterize the area and personal air concentrations of combustion byproducts produced during controlled residential fires with furnishings common in 21 st century single family structures. Area air measurements were collected from the structure during active fire and overhaul (post suppression) and on the fireground where personnel were operating without any respiratory protection. Personal air measurements were collected from firefighters assigned to fire attack, victim search, overhaul, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 71 publications
(87 citation statements)
references
References 27 publications
(38 reference statements)
6
81
0
Order By: Relevance
“…Wingfors et al [15] reported higher turnout gear/station gear workplace protection factors (WPFs) for total PAHs (WPF = 146) than naphthalene (WPF = 49), the most volatile PAH that exists predominantly in gas phase during firefighting. In a previous publication, our group reported median personal air concentrations of benzene for the attack and search firefighters of 40 and 38 ppm, respectively [5]. Median personal air concentrations of total PAHs for the attack and search firefighters were 23.8 and 17.8 µg/m 3 , respectively, and naphthalene accounted for~50% of the total [5].…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Wingfors et al [15] reported higher turnout gear/station gear workplace protection factors (WPFs) for total PAHs (WPF = 146) than naphthalene (WPF = 49), the most volatile PAH that exists predominantly in gas phase during firefighting. In a previous publication, our group reported median personal air concentrations of benzene for the attack and search firefighters of 40 and 38 ppm, respectively [5]. Median personal air concentrations of total PAHs for the attack and search firefighters were 23.8 and 17.8 µg/m 3 , respectively, and naphthalene accounted for~50% of the total [5].…”
Section: Discussionmentioning
confidence: 83%
“…In a previous publication, our group reported median personal air concentrations of benzene for the attack and search firefighters of 40 and 38 ppm, respectively [5]. Median personal air concentrations of total PAHs for the attack and search firefighters were 23.8 and 17.8 µg/m 3 , respectively, and naphthalene accounted for~50% of the total [5]. Given the high concentrations of benzene and PAHs in the fire atmosphere, even a small percentage of penetration through or around the interfaces of turnout gear could result in toxicologically relevant levels on skin.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations